Hemagglutinin and neuraminidase containing virus-like particles produced in HEK-293 suspension culture: An effective influenza vaccine candidate. Issue 29 (17th June 2016) - Venereo-Sanchez, Alina; Gilbert, Renald; Simoneau, Melanie; Caron, Antoine; Chahal, Parminder; Chen, Wangxue; Ansorge, Sven; Li, Xuguang; Henry, Olivier; Kamen, Amine
Highlights: Development of stable cell line expressing hemagglutinin and neuraminidase (293HA-NA). Gag HIV-1 protein is more efficient than M1 to induce VLPs production in 293HA-NA cells. Influenza VLPs production using Gag as scaffold was evaluated in a 3-L bioreactor and purified. Characterization of VLPs showed typical size and morphology of HIV-1 immature particles. The immunogenicity and protective efficacy of the VLPs was demonstrated in mice. Abstract: Virus-like particles (VLPs) constitute a promising alternative as influenza vaccine. They are non-replicative particles that mimic the morphology of native viruses which make them more immunogenic than classical subunit vaccines. In this study, we propose HEK-293 cells in suspension culture in serum-free medium as an efficient platform to produce large quantities of VLPs. For this purpose, a stable cell line expressing the main influenza viral antigens hemagglutinin (HA) and neuraminidase (NA) (subtype H1N1) under the regulation of a cumate inducible promoter was developed (293HA-NA cells). The production of VLPs was evaluated by transient transfection of plasmids encoding human immunodeficiency virus (HIV) Gag or M1 influenza matrix protein. To facilitate the monitoring of VLPs production, Gag was fused to the green fluorescence protein (GFP). The transient transfection of the gag containing plasmid in 293HA-NA cells increased the release of HA and NA seven times more than its counterpart transfected with the M1 encoding plasmid. Consequently, the production of HA-NA containing VLPs using Gag as scaffold was evaluated in a 3-L controlled stirred tank bioreactor. The VLPs secreted in the culture medium were recovered by ultracentrifugation on a sucrose cushion and ultrafiltered by tangential flow filtration. Transmission electron micrographs of final sample revealed the presence of particles with the average typical size (150–200 nm) and morphology of HIV-1 immature particles. The concentration of the influenza glycoproteins on the Gag-VLPs was estimated by single radial immunodiffusion and hemagglutination assay for HA and by Dot-Blot for HA and NA. More significantly, intranasal immunization of mice with influenza Gag-VLPs induced strong antigen-specific mucosal and systemic antibody responses and provided full protection against a lethal intranasal challenge with the homologous virus strain. These data suggest that, with further optimization and characterization the process could support mass production of safer and better-controlled VLPs-based influenza vaccine candidate.